2015
DOI: 10.1155/2015/195096
|View full text |Cite
|
Sign up to set email alerts
|

In VitroStudies of Bacterial Cellulose and Magnetic Nanoparticles Smart Nanocomposites for Efficient Chronic Wounds Healing

Abstract: The quality of life of patients with chronic wounds can be extremely poor and, therefore, over the past decades, great efforts have been made to develop efficient strategies to improve the healing process and the social impact associated with these conditions. Cell based therapy, as a modern tissue engineering strategy, involves the design of 3D cell-scaffold bioconstructs obtained by preseeding drug loaded scaffolds with undifferentiated cells in order to achieve in situ functional de novo tissue. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 36 publications
2
23
0
1
Order By: Relevance
“…Transmission Electron Microscope analysis of the deployed Fe(III)-coated pumice slurries amended with electron donors indicated the presence of spherical nanoparticles with a diameter of 6 nm consistent with the morphological features of magnetite (Galateanu et al, 2015; Figure 6A). These morphological features are similar to the TEM images of biogenic magnetite crystals observed by Cutting et al (2009), where akaganeite was reduced to magnetite by Geobacter sulfurreducens in cultures amended with 10 µm AQDS and 20 mM sodium acetate, and incubated for 6 days.…”
Section: Mineralogical Changes In Deployed and Incubated "Microbe Baits"mentioning
confidence: 61%
“…Transmission Electron Microscope analysis of the deployed Fe(III)-coated pumice slurries amended with electron donors indicated the presence of spherical nanoparticles with a diameter of 6 nm consistent with the morphological features of magnetite (Galateanu et al, 2015; Figure 6A). These morphological features are similar to the TEM images of biogenic magnetite crystals observed by Cutting et al (2009), where akaganeite was reduced to magnetite by Geobacter sulfurreducens in cultures amended with 10 µm AQDS and 20 mM sodium acetate, and incubated for 6 days.…”
Section: Mineralogical Changes In Deployed and Incubated "Microbe Baits"mentioning
confidence: 61%
“…In an independent study, the bacterial cellulose incorporated with Fe 3 O 4 MNPs has been used for treatment of chronic wounds. The nanocomposites have been found to be biocompatible to human adipose stem cells in terms of viability, cytotoxicity, proliferation and cellular morphology (Galateanu et al 2015).…”
Section: Wound Healing and Skin Repairmentioning
confidence: 99%
“…Owing to its unique properties, BC has found application in a number of fields such as the paper and textile industry (7), diaphragms for electro-acoustic transducers, the food industry (9, 10), film coatings as drug delivery systems (11), pharmaceuticals and cosmetics, optically transparent composites (12,13), substrates for OLEDs (13), biomaterials in cosmetics and medicine (11,(14)(15)(16). In recent years, biomedical applications of BC have received considerable attention in the literature, particulary in wound dressing, blood vessels, vascular grafts and delivery systems of drugs and proteins (17).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biomedical applications of BC have received considerable attention in the literature, particulary in wound dressing, blood vessels, vascular grafts and delivery systems of drugs and proteins (17). Various studies have proven the application of BC scaffolds in the field of tissue engineering and wound healing (15). Saska et al (2011) reported that BC composites containing hydroxyapatite showed bone regeneration properties and could ideally be used as bone grafts (16).…”
Section: Introductionmentioning
confidence: 99%